2016
DOI: 10.3109/10253890.2016.1160280
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress is a risk factor for excessive alcohol drinking and impulsivity in adults and is mediated via a CRF/GABAA mechanism

Abstract: Childhood stress and trauma are associated with substance use disorders in adulthood, but the neurological changes that confer increased vulnerability are largely unknown. In this study, maternal separation [MS] stress, restricted to the pre-weaning period, was used as a model to study mechanisms of protracted effects of childhood stress/traumatic experiences on binge drinking and impulsivity. Using an operant self-administration model of binge drinking and a delay discounting assay to measure impulsive-like b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 78 publications
(113 reference statements)
4
51
0
1
Order By: Relevance
“…In fact, alcohol withdrawal increases CRF synthesis and release in CeA (Funk et al, 2006; Roberto et al, 2010; Sommer et al, 2008), which in turn can regulate GABAergic transmission (Roberto, Gilpin, & Siggins, 2012). Moreover, alterations in the CRF system induced by stressors, such as maternal separation, are predictive of binge drinking and impulsivity behaviors in adulthood (Gondré-Lewis et al, 2016). The involvement of all these molecules in mediating neurobiological responses induced by both alcoholism and stress disorders are well documented.…”
Section: Common Molecules Of Alcohol Addiction and Stressmentioning
confidence: 99%
“…In fact, alcohol withdrawal increases CRF synthesis and release in CeA (Funk et al, 2006; Roberto et al, 2010; Sommer et al, 2008), which in turn can regulate GABAergic transmission (Roberto, Gilpin, & Siggins, 2012). Moreover, alterations in the CRF system induced by stressors, such as maternal separation, are predictive of binge drinking and impulsivity behaviors in adulthood (Gondré-Lewis et al, 2016). The involvement of all these molecules in mediating neurobiological responses induced by both alcoholism and stress disorders are well documented.…”
Section: Common Molecules Of Alcohol Addiction and Stressmentioning
confidence: 99%
“…Removing the AUD-oriented borderline PD criterion #4 from the analysis, antisocial PD criterion #1 (violations of social norms for lawful behavior) emerged from the remaining 79 criteria (Rosenström et al 2018). These criteria are likely to be associated with intermediate phenotypes related to impulsivity that follow from childhood SLEs (Castellanos-Ryan et al 2011; White et al 2014; Barker et al 2015; Gondré-Lewis et al 2016; Mackey et al 2017). On the other hand, these PD traits could also invoke adulthood SLEs, which then increase AUD risk (Boden et al 2014; Kim et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tiruveedhula, et al (2015) reported that 3-ISOPBC decreased alcohol consumption in a maternally deprived rodent model. Gondre-Lewis et al (2016) reported a similar effect with 3-PBC and proposed some involvement of α2-receptor subunits; however, this effect could not be reversed by administration of flumazenil. Consequently, this cannot be due to an effect at α2β 2/3 γ2 benzodiazepine GABA A receptors.…”
Section: Discussionmentioning
confidence: 82%
“…Knockout mice without the GABA A α1 receptor have been shown to consume less alcohol under a two-bottle alcohol versus water choice procedure (Blednov et al, 2003) and an operant self-administration procedure (June et al, 2007). The GABA A α1-preferring antagonist 3-PBC has been shown to decrease alcohol self-administration in rodents bred for high alcohol intake (Harvey et al, 2002), as well as binge-like drinking in a maternally deprived rodent model (Gondre-Lewis et al, 2016). A similar reduction in alcohol maintained responding was observed following administration of 3-ISOPBC in the maternal deprivation model (Tiruveedhula et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation